(untitled) (Training and Practice : Journal of Educational Sciences, 2017)
Views about children and education have been changing continuously throughout history. Nowadays education and development are based on understanding the children, and this is an interactive process built upon mutual communication. The study shows students’ views regarding the concept of good manners, and their opinion about their school, teachers and also what they thought was important in life. Learning about the attitudes of students may contribute to making the interactive nature of the educational-teaching process more conscious, to the understanding of students, and the success of the process itself.